Cambodia : Staff Report for the 2011 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
This 2011 Article IV Consultation reports that Cambodia's high degree of dollarization and largely reduced fiscal space constrain the authorities' ability to cushion shocks. Macroeconomic stability hinges on prudent fiscal policies. The mission cautioned that fiscal space is limited and that greater consolidation efforts are needed to strengthen revenue administration and prioritize spending. The outlook for external debt sustainability has improved on Cambodia's prudent track record, but potentially large contingent liabilities from public-private power sector projects need to be carefully managed.